Theoretical and experimental NMR study of protopine hydrochloride isomers - Tousek, Jaromír; Malináková, Katerina; Dostál, Jirí; Marek, Radek (Magnetic resonance in chemistry, 2005)
The 1H and 13C NMR chemical shifts of cis- and trans-protopinium salts were measured and calculated. The calculations of the chemical shifts consisted of conformational analysis, geometry optimization (RHF/6-31G** method) and shielding constants calculations (B3LYP/6-31G** method). Based on the results of the quantum chemical calculations, two sets of experimental chemical shifts were assigned to the particular isomers. According to the experimental results, the trans-isomer is more stable and its population is approximately 68%.
Keywords: protony; molekulární konformace; izotopy uhlíku; počítačová simulace; Carbon Isotopes; Molecular Conformation; isomerie; Computer Simulation; berberinové alkaloidy; chemické modely; Models, Molecular; magnetická rezonanční spektroskopie; molekulární modely; Isomerism; Benzophenanthridines; benzofenantridiny; Protons; Models, Chemical; Berberine Alkaloids; Magnetic Resonance Spectroscopy